Optimasi Pencampuran Batubara Beda Kualitas Dengan Metode Trial And Error untuk Memenuhi Kriteria Permintaan Konsumen di CV. Bara Mitra Kencana Kota Sawahlunto Sumatera Barat - Muhammad Divo; Ansosry Ansosry (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. CV. Bara Mitra Kencana Is one of the mining companies engaged in coal mining, located in the city of Sawahlunto, West Sumatra. Coal produced by CV. Bara Mitra Kencana consists of various types which are grouped based on their calorific value from different pits. These coal calories are influenced by the geological conditions of a mining location, including high quality coal, medium quality, and low quality (low quality) to determine the quality of the coal, the company interpreted the coring correlation from the results of geophysical well logging.The results of calculations using the Trial and Error Method using four parameters of coal quality and consumer demand Calculation using the Trial and Error Method approaches consumer demand (can be fulfilled).With the results of calculations using the Trial and Error Method from researchers there is a GCV 6297 Cal / gr better than the results of the Laboratory blending analysis that is 6000 Cal / gr and can approach consumer demand with GCV 6300 Cal / gr. Besides TM, ASH and TS also affect consumer demand. with TM the results of researchers 10.6% ar can be accepted because consumer demand for TM 10% ar because of the smaller quality of water contained in the coal, the better, ASH researchers' results 17.32% adb can be accepted because ASH consumer demand is 15% adb because the smaller the ash quality, the better, so is the TS where researchers get a 0.8% adb TS smaller than 0.8% adb.Keywords: Blending, Tiall and Error Method, Total Moisture, Ash, Sulfur, Calorie Value